What does a degree in geology actually mean? A systematic evaluation of courses required to earn a bachelor of science in geology in the United States. Issue 1 (2nd January 2023) - Klyce, Annie; Ryker, Katherine
Abstract: Calls have been made to determine optimal learning progressions for geology students so that best practices for teaching content knowledge and skills during an undergraduate degree can be determined. To address these calls, there first needs to be understanding of what courses are required. This study was conducted to provide a systematic evaluation of courses currently required to earn a bachelor of science degree in the field of geology. Once qualifying programs were determined using the American Geoscience Institute's Directory of Geoscience Departments, an inductive content analysis was used to determine categories representative of the most commonly required geology courses. Testing with an expert panel showed this binning system and codebook to have an interrater reliability (Fleiss' kappa) of 0.908, demonstrating that they can be applied reliably in future research to assess longitudinal changes in course requirements. The seven most commonly required courses include structure, sedimentology/stratigraphy, introductory courses, general field methods courses, introductory level historical geology courses, mineralogy and petrology. On average, 12.69 geology courses are required for a B.S. degree. A longitudinal comparison is also made here to highlight changes since Drummond and Markin's (2008 ) review, which include an increase in the frequency at which introductory, upper level seminar, research based and general field methods courses are required. The results presented provide a snapshot of the current state of the field, and allow for comparisons with content knowledge deemed a priority by the Future of Undergraduate Geoscience Education Report.